(untitled) (Research, Society and Development, 2021)
Bronfebrenner´s Bioecological Model of Human Development considers that development is a phonomen situated in context and that it should be studied as such. From this point of view, the ecological environment of the development is conceived as a series of concentric structures called: microsystem, mesosystem, exosystem and macrosystem. It is assumed that the work of parents is an exosystem that influences child develepment in relation to others. With the COVID-19 pandemic, changes are noted in the child´s ecological environment formed by his family microsystem and the exosystem constituted by the parents´work. This study aims to discuss the changes brought by the COVID-19 Pandemic to this exossytem and its possible repercussions on child development. This is a literature review of the narrative, review type, with descriptive and exploratory character and a qualitative approach. To approach the topic, the Bioecological Theory of Urie Bronfenbrenner is presented and the work of parents is discussed as an important ecological system and is implications for child develepment, considering, in particular, the changes observed in this exosystem after the COVID -19 Pandemic. According to the research findings, it is possible to state that the developmental bioecology of children has been affected by changes in this particular exosystem and its interactions with other contextual dimensions (macrosystemic and microsystemic), intergfering in the activities, relathionships and roles of each ecological environment that constitute it. The repercussions can have the most diverse effects on child development, positive and/or negative, and it is necessary to investigate them in the short or long term.